2015
DOI: 10.1371/journal.pcbi.1004328
|View full text |Cite
|
Sign up to set email alerts
|

Tipping the Scale from Disorder to Alpha-helix: Folding of Amphiphilic Peptides in the Presence of Macroscopic and Molecular Interfaces

Abstract: Secondary amphiphilicity is inherent to the secondary structural elements of proteins. By forming energetically favorable contacts with each other these amphiphilic building blocks give rise to the formation of a tertiary structure. Small proteins and peptides, on the other hand, are usually too short to form multiple structural elements and cannot stabilize them internally. Therefore, these molecules are often found to be structurally ambiguous up to the point of a large degree of intrinsic disorder in soluti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
63
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(71 citation statements)
references
References 45 publications
8
63
0
Order By: Relevance
“…Due to the associated timescales conformational change of proteins at interfaces has been less studied. For small peptides it is possible to examine changes in secondary structure associated with interfacial adsorption within timescales that can be accessed in simulation 29 . To do this for larger proteins it is necessary to use advanced simulation techniques, such as replica exchange 30 or metadynamics 31 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the associated timescales conformational change of proteins at interfaces has been less studied. For small peptides it is possible to examine changes in secondary structure associated with interfacial adsorption within timescales that can be accessed in simulation 29 . To do this for larger proteins it is necessary to use advanced simulation techniques, such as replica exchange 30 or metadynamics 31 .…”
Section: Introductionmentioning
confidence: 99%
“…The conformational behavior of htt NT closely resembles the LKa14 peptide with the amino acid sequence Ace-(LKKLLKL) 2 -Nme. 64,65 Similar to htt NT , LKa14 also possesses a large hydrophobic moment 63 in the a-helix conformation and lacks a well-defined secondary structure in dilute solution.…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with those previously reported by Dalgicdir et al which highlight that two synthetic peptides, LKKLLKLLKKLLKL (LK) and EAALAEALAEALAE (EALA), adopt neither random coil nor fully formed a-helical structure in water. [27] Using molecular dynamics simulations, the authors reported that the peptides adopt multiple conformations with short lifetimes in water. [27] As noted from Table 2, the occupancy of a basin is much higher for ion-pair peptides as compare to cationic peptides.…”
Section: Iamentioning
confidence: 99%
“…[27] Using molecular dynamics simulations, the authors reported that the peptides adopt multiple conformations with short lifetimes in water. [27] As noted from Table 2, the occupancy of a basin is much higher for ion-pair peptides as compare to cationic peptides. The occupancy in a basin is 28.5 %, 28.1 % for Ib, IIb, respectively, while the occupancy is only 19.2 %, 19.9 % for Ia, IIa, respectively.…”
Section: Iamentioning
confidence: 99%